2012
DOI: 10.1158/1535-7163.mct-11-0548
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Agonists Induce MicroRNA-335 Expression and Inhibit Lung Metastasis of Estrogen Receptor Negative Breast Cancer Cells

Abstract: The aryl hydrocarbon receptor (AHR) was initially identified as a receptor that bound 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and related environmental toxicants; however, there is increasing evidence that the AHR is an important new drug target for treating multiple diseases including breast cancer. Treatment of estrogen receptor (ER)-negative MDA-MB-231 and BT474 breast cancer cells with TCDD or the selective AHR modulator 6-methyl-1,3,-trichlorodibenzofuran (MCDF) inhibited breast cancer cell invasion in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 46 publications
(44 reference statements)
2
69
0
Order By: Relevance
“…Previous functional studies with TCDD and MCDF in breast cancer cells showed that both compounds inhibit cell migration in a Boyden chamber assay (Zhang et al, 2012). Figure 6A illustrates the effects of TCDD and the pharmaceutical AHR ligands on this response in MDA-MB-468 cells.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous functional studies with TCDD and MCDF in breast cancer cells showed that both compounds inhibit cell migration in a Boyden chamber assay (Zhang et al, 2012). Figure 6A illustrates the effects of TCDD and the pharmaceutical AHR ligands on this response in MDA-MB-468 cells.…”
Section: Resultsmentioning
confidence: 91%
“…A ChIP assay was used to compare TCDD-induced recruitment of the AHR to the proximal CYP1A1-DRE promoter (Zhang et al, 2012) with that observed for 4-hydroxytamoxifen (Fig. 5A), mexiletine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations